Indonesian Pharmaceutical Companies: Capital Structure, Business Risk, Company Value and Firm Size as A Moderating Variable Analysis - Anisah Anisah; Moh. Ali Murad; Asriadi Asriadi; Suryadi Samudra; Dilah Magfirah (CV. Ridwan Publisher, 2023)
This study looks into how firm size affects the relationship between capital structure and business risk in determining firm value. This study makes use of panel data from ten pharmaceutical companies sourced from their annual reports from 2015 to 2021. The data analysis method employed the Structure Equation Modeling (SEM) method via the Partial Least Squares (PLS) method with WarpPLS 6.0 software. According to the findings of this study, capital structure had no effect on firm value, whereas business risk had a significant negative effect on firm value. Only firm size can moderate the relationship between capital structure and firm value. Thus, managers' primary concern in order to maximize the value of pharmaceutical companies in Indonesia is to ensure that the amount of income received by the company remains stable in order to avoid income volatility, which can trigger increased business risk for the company. Furthermore, when developing a policy to determine how much debt or equity is used to finance the company in order to maximize the company's value, the size of the company must be considered.